The Differences in Viral Etiologies between Children with and without Severe Disability Admitted to the Pediatric Intensive Care Unit with Acute Respiratory Illness - Karaarslan, Utku; Topal, Sevgi; Ayhan, Yüce; Ağın, Hasan (Journal of Pediatric Infectious Diseases, 2020)
Objectives The objectives of this study were to evaluate the differences in the viral etiologies and variability in the clinical course between children with and without severe disability (SD) admitted to the pediatric intensive care unit (PICU) with acute respiratory illness (ARI).Methods The medical records of patients admitted to our PICU between June 2017 and July 2019 were retrospectively reviewed for viral etiology and clinical course.Results Forty-eight of 136 patients included in the study had SD. The rates of requiring positive pressure ventilation (43.5% vs. 20.5%) or inotropic support (39.9% vs. 15.9%), and the median length of stay (11 [10] vs. 5 [8]) were significantly higher in children with SD (p < 0.01, each). Influenza infection was significantly higher in children with SD (20.8% vs. 2.3%; p < 0.01) whereas respiratory syncytial virus (RSV) infection was more common in children without SD (47.7% vs. 4.2%; p < 0.01). There was no statistically significant difference in terms of other viruses between study groups.Conclusion In this present study, influenza was an important pathogen for children with SD, while RSV was the main cause of ARI-associated PICU admission in children without SD. By focusing on increasing the rate of immunization against influenza in children with SD and their caregivers the burden of influenza-associated PICU admissions could be decreased.
Keywords: children with disability; pediatric intensive care; respiratory viruses